1981
DOI: 10.1007/bf02370039
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of physiologically active zinc in maize by biochemical assay

Abstract: The enzymes ribonuclease, aldolase and carbonic anhydrase were evaluated as biochemical assays for physiologically active zinc in maize. Seedlings were cultured for 14 or 30 days on a black-earth soil with factorial combinations of phosphorus and zinc fertilizers so as to produce in the leaves varying levels of active zinc at a constant level of total zinc. Enzyme activity was correlated with plant growth, leaf nutrient composition and the occurrence of visual symptoms of zinc deficiency.Ribonuclease and aldol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…These relationships indirectly stress the significance of both nutrients in controlling leaf photosynthetic activity and explain the importance of this plant part as a starch donor for developing grains (Rajcan and Tollenaar 1999). While the data obtained in treatments NPK + Mg can be related to the presence of Mg in the chlorophyll molecule, in those outlined from NPK + Zn, the effect of zinc on the extended length of the period of carbohydrates synthesis by leaves was reported by Gibson and Leece (1981) and Guliev et al (1992). Total nitrogen content (TNC) in maize plant parts at its physiological maturity showed the year-to-year variability, with the lowest coefficient of variation (CV) attributed to kernels and cob cores.…”
Section: Resultsmentioning
confidence: 90%
“…These relationships indirectly stress the significance of both nutrients in controlling leaf photosynthetic activity and explain the importance of this plant part as a starch donor for developing grains (Rajcan and Tollenaar 1999). While the data obtained in treatments NPK + Mg can be related to the presence of Mg in the chlorophyll molecule, in those outlined from NPK + Zn, the effect of zinc on the extended length of the period of carbohydrates synthesis by leaves was reported by Gibson and Leece (1981) and Guliev et al (1992). Total nitrogen content (TNC) in maize plant parts at its physiological maturity showed the year-to-year variability, with the lowest coefficient of variation (CV) attributed to kernels and cob cores.…”
Section: Resultsmentioning
confidence: 90%
“…Corn is a sensitive plant to Zn deficiency. Zinc deficiency resulted in a decline in the activity of carbonic anhydrase, aldolase and ribonuclease and a declined Zn concentration and a dry matter decrease in aerial parts (shoots) in corn (Gibson and Leece, 1981). In Iran, there are greater than 400,000 hectares cultivated for corn production.…”
Section: Introductionmentioning
confidence: 99%
“…As combined soil+foliar application of Zn increased the concentration of physiologically active Zn in the leaves, it enhanced the CA activity in leaves. It was earlier reported that activity of CA decreased in many plant species as a consequence of Zn deficiency (Gibson and Leece 1981). A Zn inefficient wheat genotype when grown under Zn deficient conditions showed reduced activity of CA (Hacisalihoglu et al 2003).…”
Section: Carbonic Anhydrase (Ca) Activitymentioning
confidence: 99%